Budget as a tool of municipality`s financial economy - Starzyńska, Katarzyna (Management and Administration Journal, 2023)
Budget is the most important financial plan of the state. The article attempts to characterize the municipal budget, taking into account its specific features, types and structures. In particular, attention was paid to the advantages and disadvantages of the traditional budget.